Model Of Automatic Fire Fighting Simulation And Security System Based On Internet Of Things (IoT) And Cloud Computing In Cisco Packet Tracer - Ginting, Emilia Br; Novriyenni, Novriyenni; Syahputra, Siswan (International Journal of Informatics, Economics, Management and Science, 2025)
Fires often become disasters that can cause significant losses, both material and human lives. Fires can occur anywhere, including buildings, homes, and industries. During a fire, the risk of death or serious injury is also very high for people trapped inside a room, due to limited access to exit from the room where the fire occurs. Security is one of the most important aspects of life; everyone needs greater safety assurance regarding their home. In this research, the author employs system development and simulation methods, which allow researchers to reproduce complex environments and test system performance under various conditions without building actual physical infrastructure. Researchers have an idea to create a model and simulation of an automatic fire extinguisher and a security system based on IoT and cloud computing using Cisco Packet Tracer. The use of Cisco Packet Tracer as a simulator allows for the creation of IoT-based network simulation models to analyze the results of the simulations on the developed system, ensuring that the simulation results are accurate. The automatic fire extinguisher and security system simulation model yields positive results. When a fire is detected, the sprinkler system, alarm, and LCD provide information indicating a fire, while exit access such as doors and windows yield good simulation results. Additionally, the simulations for security systems for entrance security and rooms containing valuable items produce favorable simulation outcomes.